Investigation of fiber-based sensors for localized detection - Loo, William Lian Wei. (2013)
Fiber Optics Sensor (FOS) has been one of the hottest topics in the sensors field of study where FOS has many rooms for exploring into new ideas, new findings, new applications and new improvements.